Fonte alternativa de potássio para adubação da cana-de-açúcar - Duarte, Ivaniele Nahas (2015)
Sugarcane yield, technological parameters, soil chemical properties an leaf absorption of nutrients in plant and ratoon cane were analyzed to compare three application of thermopotash with three different granule sizes. Five experiments were done: three at sugar mills Vale do São Simão, Aroeira and Guaíra, applying potash in the cane planting furrows (K-furrow), and two were broadcast potash application in sugarcane at the mills Aroeira and Usina Guaíra. All experiments were evaluated in two agricultural years. The experimental design was randomized blocks (RBD) as factorials. The K-furrow at São Simão Mill was a 2 x 5 factorial, with two potassium sources (Termopotash-TK47 and Potassium chloride-KCl) and 5 potassium doses (0, 50, 100, 150 or 200 kg ha-1 K2O). At the mills Aroeira and Guaíra, a 2 x 3+1 factorial was used, with two potassium sources (Thermopotash-Alpha and KCl at Aroeira, and Thermopotash-Beta and KCl at Guaíra) and 3 doses (50, 100, or 200 kg ha-1 K2O), and an additional treatment that did not receive any potassium fertilization. The experiment with ratoon cane, at the São Simão mill, had the plot divided into two, and one half received 120 kg ha-1 K2O (sources TK47 and KCl) while the other received none. Broadcast potassium application, both at Aroeira and Guaíra mills, was done as a 2 x 4 +1 factorial, with two potassium sources (Alpha and KCl at Aroeira and Beta e KCl at Guaíra) and 4 potassium doses (100, 200, 400 or 800 kg ha-1 K2O) and an additional treatment with no potassium fertilization. Ratoon cane experiment, both at Aroeira and Guaíra mills, was done in split plots, in which one half received potassium as KCl and the other received none. The variables analyzed in both harvests were: leaf and soil K, Ca, Mg and Si (0-20 and 20-40 cm depths); soil pH at both depths, cane height, Brix, Pol, ATR and TAH, cane stalk yield, and relative agricultural efficacy (RAE) of Thermopotash. Quantitative treatments were submitted to regression analyses and qualitative ones were compared by the Tukey test at 5% significance. It was concluded in the five experiments that thermopotash TK47, Alpha and Beta supplied the soil and plant with calcium, magnesium and silicon, and that TK47 increased soil pH. As for termopotash RAE, TK47 was more effective than KCl for both plant cane and ratoon; RAE of Alpha was greater than KCl for ratoon cane applied both in the furrow and broadcast In contrast, RAE of Beta was greater than KCl only after the first the first harvest, when Beta was broadcast at 200 kg ha-1 K2O; however, after it was applied in the planting furrow, Beta RAE was greater than KCl only after the harvest of ratoon cane. Thermopotash TK47, Alpha and Beta brought benefits for cane production and demonstrated residual effects for ratoon cane. Localized application of potassium sources, in the cane planting furrow, at high potassium doses, can decrease plant cane yield; however, after broadcast application of treatments, cane yield increased as potassium doses increased.